2021
DOI: 10.3390/ph14010048
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Riboflavin and Rose Bengal Photosensitizer Modified Adhesive Resin for Orthodontic Bonding

Abstract: This study aimed to evaluate the effect of riboflavin (RF) and Rose Bengal (RB) photosensitizer modified adhesive resin on the degree of conversion (DC), and antimicrobial capacity after bonded to tooth surface. Different concentrations of RB and RF were prepared by homogenization method. An ultraviolet light source A (UVA) (375 nm wavelength, 3 mW/cm2 power) was used for 30 min irradiation. FTIR was performed for control and test adhesives to analyze the DC. Antibacterial testing was performed using the MTT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Many in vitro and in vivo studies present high efficiency of aPDT against microorganisms involved in dental caries [13,[33][34][35][36][37]. The results of Alqerban [38] study showed that not only aPDT with Riboflavin and Rose Bengal can be used for bonding orthodontic brackets to the tooth surface but also revealed the substantial antibacterial properties against S. mutans. Hugo Panhóca et al [39] reported aPDT with Curcumin reduces the number of living cells of S. mutans in a biofilm model created on the surface of metallic orthodontic accessories.…”
Section: Discussionmentioning
confidence: 99%
“…Many in vitro and in vivo studies present high efficiency of aPDT against microorganisms involved in dental caries [13,[33][34][35][36][37]. The results of Alqerban [38] study showed that not only aPDT with Riboflavin and Rose Bengal can be used for bonding orthodontic brackets to the tooth surface but also revealed the substantial antibacterial properties against S. mutans. Hugo Panhóca et al [39] reported aPDT with Curcumin reduces the number of living cells of S. mutans in a biofilm model created on the surface of metallic orthodontic accessories.…”
Section: Discussionmentioning
confidence: 99%
“…Many in vitro and in vivo studies present high e ciency of aPDT against microorganisms involved in dental caries [33][34][35][36][37][38] . The results of Alqerban 39 study showed that no only aPDT with Ribo avin and Rose Bengal can be used for bonding orthodontic brackets to the tooth surface but also revealed the substantial antibacterial properties against S. mutans. Hugo Panhóca et al 40 reported aPDT with Curcumin reduces the number of living cells of S. mutans in a bio lm model created on the surface of metallic orthodontic accessories.…”
Section: Discussionmentioning
confidence: 99%
“…Algerban et al demonstrated that the metabolic activity of S. mutans significantly decreased with the addition of a high amount of either rose bengal or riboflavin, with a light source for illumination (375 nm, 3 mW/cm 2 ). The metabolic activity of 0.1% rose bengal or riboflavin after APDT reduced to a certain extent on the 30th day, and 0.5% of either rose bengal-APDT or riboflavin-APDT showed relatively reduced viability of S. mutans well under 35% [65].…”
Section: Application Of Natural Photosensitizers In Orthodontic Systemmentioning
confidence: 94%